Radiographic and microscopic evaluation of the efficacy of two different techniques in obt-uration of internal resorption defects (An in vitro comparative study) - Ragheed M Basheer (University of Mosul, College of Dentistry, 2005)
ABSTRACT This study was designed to determine the effectiveness of lateral compaction and ultrasonic condensation obturation techniques for internal resorption defects, for which 20 extracted human maxillary central incisors teeth were selected. They were instrumented up to size 55 file. Their roots were sectioned transversely 6 mm from the apex and hemicircular cavities were prepared in both sections using #6 round bur. The sections were glued back together using cyanoacrylate thus obtaining root canal with cavities simulating internal resorption. The teeth were randomly divided into 2 groups of 10 teeth each. The following obturation techniques were evaluated: Lateral compaction (Group I), and ultrasonic condensation (Group II). Ultrasonic condensation gave good results. Obturated internal resoption defects were filled mainly with gutta percha. Statistical analysis showed that there was significant difference between Groups I and II. Results with lateral condensation were inferior compared to ultrasonic condensation technique for obturation of simulated internal resorption defects Therefore, the latter technique is recommended to be used to obturate the defects of internal resorption defects in clinical practice.